2016
DOI: 10.1212/wnl.0000000000002481
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in comorbidity at diagnosis of multiple sclerosis

Abstract: Objective:To determine the prevalence of comorbidity in the multiple sclerosis (MS) population at the time of MS diagnosis. We also compared the prevalence of comorbidity in the MS population to that in a matched cohort from the general population.Methods:Using population-based administrative health data from 4 Canadian provinces, we identified 23,382 incident MS cases and 116,638 age-, sex-, and geographically matched controls. We estimated the prevalence of hypertension, diabetes, hyperlipidemia, heart disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
86
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 33 publications
10
86
0
3
Order By: Relevance
“…While most of the studies of comorbidity prevalence focused on prevalent MS cohorts, several focused on cohorts of persons with newly diagnosed MS. Among these individuals, the most common physical comorbidities are hypertension, chronic lung disease and hyperlipidemia [20,21]. Moreover, the prevalence of multiple comorbidities is higher in the MS population than in an age-, sex-and geographically-matched non-MS population at least five years before MS diagnosis [20].…”
Section: Prevalence Of Comorbidity In Multiple Sclerosismentioning
confidence: 99%
“…While most of the studies of comorbidity prevalence focused on prevalent MS cohorts, several focused on cohorts of persons with newly diagnosed MS. Among these individuals, the most common physical comorbidities are hypertension, chronic lung disease and hyperlipidemia [20,21]. Moreover, the prevalence of multiple comorbidities is higher in the MS population than in an age-, sex-and geographically-matched non-MS population at least five years before MS diagnosis [20].…”
Section: Prevalence Of Comorbidity In Multiple Sclerosismentioning
confidence: 99%
“…This study demonstrated the involvement of the same HLA alleles in MS and schizophrenia, but with an opposite directionality of effect. Intriguingly, recent population-based studies found that several psychiatric comorbidities including schizophrenia, anxiety, depression, and bipolar disorder were more common in MS population than in a matched control cohort (79, 80), as were white matter changes and myelin-related dysfunction in schizophrenia (81). …”
Section: Vitamin-d In Schizophreniamentioning
confidence: 99%
“…6 Depresyon, MS'de diğer kronik nörolojik hastalıklara göre daha sık görülmektedir. 4 Johansson ve ark.nın, yakın zamanda yapmış oldukları ça-lışmada, MS hastalarında depresyonun görülme sıklığının arttığı sonucuna ulaşmışlardır. 8 Bu sonucun nedenlerini de hastalığın inflamatuar mekanizması ve ayrıca hastaların karşılaştığı fiziksel ve sosyal zorluklar olarak bildirmişlerdir.…”
Section: Multi̇pl Skleroz Ve Majör Depresi̇f Bozuklukunclassified
“…Erkek hastalarda diyabet, epilepsi, depresyon ve anksiyete kadınlara göre daha yük-sek prevalansta saptanmıştır. 4 Hastalığın patofizyolojisindeki inflamasyonun çalışmalarda psikiyatrik hastalıklara zemin oluş-turduğu saptanmışsa da nörolojik açıdan engellilik ve hayat kalitesinin düşmesi, hastalarda özellikle depresyon ve anksiyetenin görülme sıklığını artırmaktadır. 5,6 Bu çalışmada, MS'de görülen psikiyatrik bulgular ve bozukluklar, yaklaşım ve patofizyolojisi tartışılmıştır.…”
unclassified